THE NATURE OF MOLECULAR CLOUD MATERIAL IN INTERPLANETARY DUST - Keller L.P.; Messenger S.; Flynn G.J.; Clemett S.; Wirick S.; Jacobsen C. (My University, 2004)
Eight interplanetary dust particles (IDPs) exhibiting a wide range of H and N isotopic anomalies have been studied by transmission electron microscopy, x-ray absorption near-edge structure spectroscopy, and Fourier-transform infrared spectroscopy. These anomalies are believed to have originated during chemical reactions in a cold molecular cloud that was the precursor to the Solar System. The chemical and mineralogical studies reported here thus constitute direct studies of preserved molecular cloud materials. The H and N isotopic anomalies are hosted by different hydrocarbons that reside in the abundant carbonaceous matrix of the IDPs. Infrared measurements constrain the major deuterium (D) host in the D-enriched IDPs to thermally labile aliphatic hydrocarbon groups attached to macromolecular material. Much of the large variation observed in D/H in this suite of IDPs reflects the variable loss of this labile component during atmospheric entry heating. IDPs with elevated 15N/14N ratios contain N in the form of amine (-NH2) functional groups that are likely attached to other molecules such as aromatic hydrocarbons. The host of the N isotopic anomalies is not as readily lost during entry heating as the D-rich material. Infrared analysis shows that while the organic matter in primitive anhydrous IDPs is similar to that observed in acid residues of primitive chondritic meteorites, the measured aromatic:aliphatic ratio is markedly lower in the IDPs.